Kronecker Method With Generalized And Application - Rasha Thnoon Taieb Alrawi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The aim of this paper is to study the Kronecker method then we explain the relationship between proposed method and the matrix. Also we can be generalize this method on the matrix and we give some examples for clear this method and importance in solving a lot of problems.